Content analyses of alcohol-related images during television broadcasts of major sports events in New Zealand. Issue 3 (7th August 2017) - Gee, Sarah; Sam, Michael P.; Jackson, Steve J.
Abstract : This paper examines the nature, frequency and duration of alcohol-related promotions during major sports events in New Zealand revealing that sponsorship and activation-related activities of alcohol brands subvert national regulations that ban alcohol advertising during daytime television programming. Abstract : Purpose: The purpose of this paper is to examine the nature, frequency, and duration of alcohol-related promotions and crowd alcohol consumption during major sports events broadcasted on the SKY Sport network between September 2011 and February 2012. Design/methodology/approach: Content analyses for various categories of alcohol-related images were conducted, including a novel inclusion of analysing crowd alcohol consumption. Findings: The results provide empirical evidence that sponsorship and activation-related activities of alcohol brands subvert national regulations that ban alcohol advertising during daytime television programming. Originality/value: The results serve to sensitise researchers, practitioners, policy makers, and regulators to the prevalence of incidental alcohol promotional material within the overall televised alcohol advertising mix and the broader societal exposure to such images. This research also informs readers that alcohol companies and media outlets produce alcohol-related marketing that may not be in-line with the meaning and/or intent of laws.